Memory retention of appetitive and aversive conditioning in the damselfish Stegastes fuscus. Issue 3 (18th June 2019) - Silveira, Mayara M.; Ferreira de Souza, Jéssica; Pires Moreira, Ana L.; Silva, Priscila F.; Luchiari, Ana C.
Abstract: We compared the memory of damselfish Stegastes fuscus in an aversive and appetitive conditioning task. Fish were trained to associate the sides of the tank that corresponded to the presence of a positive (conspecific presence) or negative (electroshock) stimulus. After two conditioning sessions, they were tested for learning. The fish conditioned to the stimulus were then re‐tested for memory retention after 5, 10 or 15 days. Both the positive and negative rewards were associated with a specific side of the tank, indicating learning ability. Additionally, in both contexts, S. fuscus stored the information learned and showed similar behavioural patterns after 5, 10 and 15 days, suggesting long‐lasting memory. For the ecological context, long lasting memories of social encounters outcomes and negative experiences of threatening situations may confer advantages that ultimately affect fishes' fitness.